2007
DOI: 10.2139/ssrn.999354
|View full text |Cite
|
Sign up to set email alerts
|

On the Optimal Relation between the Properties of Managerial and Financial Reporting Systems

Abstract: We develop a theoretical model of the …rm that links properties (stewardship vs. valuation focus) of …nancial reporting regimes with the informational properties of optimal managerial accounting systems. We show that, contrary to the standard textbook proposition, properties of management and …nancial accounting systems are not independent. Signi…cantly, we provide an explicit connection between exogenous and observable properties of a …rm's …nancial reporting system and the quality of the managerial accountin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 16 publications
2
23
0
1
Order By: Relevance
“…4 Extant research has examined topics such as earnings management in the context of IPOs (Aharony et al, 1993;Friedlan, 1994;Teoh et al, 1998), change in corporate governance practices triggered by IPOs (Burton et al, 2004), issues related to disclosure in IPO prospectuses (Clarkson et al, 1992;Mather, et al, 2000;Shi et al, 2013), and the effects of IPOs on the financial performance of listed companies (Jain and Kini, 1994). However, studies examining how IPOs influence the MA practices of newly listed firms are relatively rare, despite the close linkages between management accounting, financial accounting, and corporate governance (Bhimani, 2009;Hemmer and Labro, 2008;Merchant and Van der Stede, 2012).…”
Section: Ipos and Management Accountingmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Extant research has examined topics such as earnings management in the context of IPOs (Aharony et al, 1993;Friedlan, 1994;Teoh et al, 1998), change in corporate governance practices triggered by IPOs (Burton et al, 2004), issues related to disclosure in IPO prospectuses (Clarkson et al, 1992;Mather, et al, 2000;Shi et al, 2013), and the effects of IPOs on the financial performance of listed companies (Jain and Kini, 1994). However, studies examining how IPOs influence the MA practices of newly listed firms are relatively rare, despite the close linkages between management accounting, financial accounting, and corporate governance (Bhimani, 2009;Hemmer and Labro, 2008;Merchant and Van der Stede, 2012).…”
Section: Ipos and Management Accountingmentioning
confidence: 99%
“…A substantial amount of research has revealed that IPOs may trigger significant changes to the ownership structure, corporate governance, and financial reporting practices of newly listed firms (Aharony et al, 2000;Burton et al, 2004;Ernst & Young, 2008;Hung et al, 2012;Lee, 2001;Teoh et al, 1998). However, despite the close linkages between management accounting, financial accounting, and corporate governance (Bhimani, 2009;Hemmer and Labro, 2008;Merchant and Van der Stede, 2012), research into the effect of IPOs on the management accounting (MA) practices of newly listed firms is relatively limited and the findings generated so far appear inconclusive and partial. First, there is evidence that IPOs may facilitate changes in the planning and control, performance measurement, and capital budgeting of newly listed companies (Kraus and Strömsten, 2012;Von Eije et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…[8] Given that the link between financial and management accounting information is of higher importance in financiallyoriented management control systems than in technically oriented ones, this would -once again -call for an integrated rather than a separate accounting system design. Nevertheless, how and why changes towards a financially-oriented management control system also induce changes in the management accounting system has not yet been explored (Hemmer and Labro, 2008;Lambert, 2007;Ittner and Larcker, 2001). [9] David Hurwitz (2003) discussed the challenges and opportunity of 21st century IT and the rise of portfolio management in the IT world.…”
Section: Survey Of Literaturementioning
confidence: 99%
“…There was no discussion of the technology platform and technology skill needed for supporting the IFRS based system. [11] Kim Smith (2002) focused on the effect of e-business/ecommerce as a current development in the audit and the role of the auditor in tackling internet e-com. The author claims that the auditor should perform the internet e-com audit as per any other audit of financial statements.…”
Section: Communications On Applied Electronics (Cae) -Issn : 2394-471mentioning
confidence: 99%
“…Staré účetní paradigma pomalu umírá a uvolňuje cestu novému. V neposlední řadě je nutné zmínit tendence prorůstání manažerského a finančního účetnictví (Hemmer a Labro, 2008), kdy i v rámci účetních závěrek určených pro potřeby externích uživatelů se zveřejňují informace používané pro vnitřní řízení a založené na tzv. manažerském přístupu (např.…”
Section: Tabulka 7 Ekonomické Pojetí Zisku a Jeho Vlastnostiunclassified